Effect of combined application of herbicides with retardants depending on Triticum aestivum L. growth stage - Kieloch, Renata; Domaradzki, Krzysztof (Polish Journal of Agronomy, 2022)
In 2013–2016 the possibility of combined application of herbicides with retardants in winter wheat was investigated in Institute of Soil Science and Plant Cultivation in Wrocław. Two retardants (1. chloromequate chloride, 2. trinexapac-ethyl) were used in tank mixture with fluroxypyr and florasulam + amino- pyralide. The mixtures were applied on two dates: 1. at the end of tillering, 2. at the stage of 1–2 nodes (florasulam + amino- pyralide) or at the stage of flag leaf (fluroxypyr). Efficacy of weed control was affected only by date of treatment. Irrespective of which herbicide-retardant combination was used, the weed sup- pression was the lowest on plots treated with the mixtures at a later growth stage. It was reflected in the size of grain yield re- ceived from these plots, that was comparable to untreated control. Application of the mixture of fluroxypyr with trinexapac-ethyl in winter wheat tillering and flag leaf growth stages contributed to seed uniformity decrease.